ANALISIS SISTEM DAN PERANAN KELEMBAGAAN SEKTOR PERUMAHAN DI KABUPATEN JEMBER: PARADIGMA NEW INSTITUTIONAL ECONOMICS (NIE) - Kristiyanto, Sony (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
New Institutional Economics showed that institutions are not only focused on the institutions but the rules of the game in economic activity between actors in the Real estate  sector, both formal and informal institutions. This study aims to determine the role of the institutional system and the real estate  industry in Jember District. Key informants were selected using the snowball method. The data analysis technique use the Analysis Hierarchy Process (AHP). This study shows that the institutional system of the Real estate  industry in Jember is dominated by institutional formal than informal institutions. Formal institutions providing legal protection and means of coordination for all developers with other developers, government and society as a prospective buyer. Formal institutions play a greater role than in the informal institutional entire activity in the real estate  industry in Jember.